PERCEPTION FACTORS OF PEDESTRIAN TRANSIT ORIENTED DEVELOPMENT (TOD) DUKUH ATAS - Muhammad Zaidanur Rizqi; Nurhikmah Budi Hartanti (International Journal on Livable Space, 2020)
The concept of walkability is the right solution for increasing walking activities and solving various transportation problems. The function of TOD is to facilitate and accommodate public needs related to mobility which prioritizes pedestrian accessibility. This study aims to determine the factors influencing the pedestrians’ perception in the TOD Dukuh Atas area. The quantitative analysis of perceptual data measured using a Likert scale will be compared with the walkability index value based on a qualitative assessment using the Global Walkability Index (GWI) framework. The results showed that there was a difference between the value of GWI and pedestrian perceptions value. It means that the GWI is not fully compatible with the Indonesian pedestrian culture.